2008
DOI: 10.1080/03052150802054035
|View full text |Cite
|
Sign up to set email alerts
|

Economic design of water distribution systems in buildings

Abstract: This paper discusses an engineering optimization problem which arises in hydraulics and is related to the use of a new criterion for sizing water distribution piping in large buildings. The optimization model aims to find the most suitable interior pipe diameters for the various pipes in the system, using commercial sizes and minimizing the overall installation cost according to some boundary conditions. The problem is formulated as a nonconvex nonlinear program and a branch-and-bound algorithm is introduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…These values, for both EM and hybrid EM algorithms, are Table 12 under the columns headed by "real". These results are equal to those reported in [16] where a branch-and-bound type algorithm is used. The solution obtained by the hybrid EM algorithm required 184577 function evaluations and the EM algorithm needed 174331 function evaluations (for a population of 210 points).…”
Section: Design Of a Water Distribution Systemsupporting
confidence: 78%
See 3 more Smart Citations
“…These values, for both EM and hybrid EM algorithms, are Table 12 under the columns headed by "real". These results are equal to those reported in [16] where a branch-and-bound type algorithm is used. The solution obtained by the hybrid EM algorithm required 184577 function evaluations and the EM algorithm needed 174331 function evaluations (for a population of 210 points).…”
Section: Design Of a Water Distribution Systemsupporting
confidence: 78%
“…The last problem is related with the design of a water distribution system in a building. The case herein solved is fully described in [16] and has 21 pipes. The decision variables x i , i = 1, .…”
Section: Design Of a Water Distribution Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Ostfeld et al developed and demonstrated an ant colony methodology for the least-cost design of gravitational water distribution systems with a single loading case [5], to the conjunctive least-cost design and operation of multiple loading pumping water distribution systems. Judice et al discussed an engineering optimization problem that arises in hydraulics and was related to the use of a new criterion for sizing water distribution piping in large buildings [6]. The optimization model aimed to find the most suitable interior pipe diameters for the various pipes in the system, using commercial sizes and minimizing the overall installation cost according to some boundary conditions.…”
Section: Literature Reviewmentioning
confidence: 99%